«Rodari the educationist» today, and the rights of the child - Benetton, Mirca (Studi sulla Formazione/Open Journal of Education, 2019)
The purpose of this contribution is to explore the educationist thinking of children’s writer Gianni Rodari and assess its relevance to today, approaching the centenary of his birth (1920), and with the Convention on the Rights of the Child (CRC, 1989) now in its thirtieth year. The question is whether, and how, the ideas of Rodari the educationist and his vision of what a good educationist might be — as clearly stated and analyzed by Franco Cambi in Rodari pedagogista (1990) — have been embraced and promoted.